Influences of social environment on farmers’ behavioural to practice an agricultural technology, screenhouse: An application of social cognitive theory - Hikmah, Nailul; Sarwoprasodjo, Sarwiti; Indraningsih, Kurnia Suci (Technium Social Sciences Journal, 2023)
Climate change has a high impact on the agricultural sector, especially horticulture farming which aims to increase the welfare of farmers. Screenhouse technology can be a solution to increase the productivity and quality of agricultural products. This study is aimed to analyse the behaviour of farmers in imitating the model of applying the screen house for horticultural crop cultivation (decorative plants and vegetables) and to analyse the factors that influence farmer behaviour in imitating the model of applying the screen house for the cultivation of horticultural crops (decorative plants and vegetables). This study used the Social Cognitive theory by Albert Bandura. The research was conducted using a quantitative approach to the survey method. Data were taken through interviews using a questionnaire to 70 farmers who already knew or did not know screenhouse technology and were analysed using Partial Least Square (PLS) Structural Equation Modeling (SEM). The results showed that the influence of personal factors on the behaviour of applying screen house technology was 0.572, the influence of environmental factors on farmer behaviour was 0.255, personal factors had an influence on environmental factors by 0.595, and personal factors were mediated by environmental factors on farmer behaviour by 0.152. This study concluded that there was a real influence between personal factors on environmental factors, personal factors on farmer behaviour, environmental factors on farmer behaviour, and personal factors on farmer behaviour mediated by environmental factors.